2013
DOI: 10.1371/journal.pone.0066328
|View full text |Cite
|
Sign up to set email alerts
|

Serum Fucosylated Haptoglobin as a Novel Diagnostic Biomarker for Predicting Hepatocyte Ballooning and Nonalcoholic Steatohepatitis

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a growing medical problem around the world. NAFLD patients with nonalcoholic steatohepatitis (NASH) can develop cirrhosis and hepatocellular carcinoma. The ability to distinguish NASH from simple steatosis would be of great clinical significance. Ballooning hepatocytes are characteristic of typical pathological NASH; here, the polarized secretion of proteins is disrupted due to destruction of the cytoskeleton. We previously reported that fucosylated glycoproteins are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 42 publications
(54 reference statements)
5
64
0
Order By: Relevance
“…Yu et al [42] performed a serum protein fingerprint analysis, utilising the SELDI-TOF-MS technique combined with bioinformatic approaches and discovered that haemoglobin subunit alpha was significantly up-regulated in NAFLD group. It has been proposed that the relationship between serum haemoglobin and NAFLD may be partially modulated by haptoglobin (Hpt), an α2-glycoprotein acute phase protein produced in response to an inflammatory insult [44] . Serum haemoglobin levels may be a marker of hepatic steatosis but not of severity of NAFLD in obese patients.…”
Section: Extracellular Matrixmentioning
confidence: 99%
See 4 more Smart Citations
“…Yu et al [42] performed a serum protein fingerprint analysis, utilising the SELDI-TOF-MS technique combined with bioinformatic approaches and discovered that haemoglobin subunit alpha was significantly up-regulated in NAFLD group. It has been proposed that the relationship between serum haemoglobin and NAFLD may be partially modulated by haptoglobin (Hpt), an α2-glycoprotein acute phase protein produced in response to an inflammatory insult [44] . Serum haemoglobin levels may be a marker of hepatic steatosis but not of severity of NAFLD in obese patients.…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…A recent study by Kamada et al [44] has shed a light into the role of acute phase protein and progression of NAFLD. Kamada et al [44] utilised lectin antibody enzymelinked immunosorbent assay (ELISA) and demonstrated that serum fucosylated haptoglobin (Fuc-Hpt) underwent a stepwise increased with increasing hepatocyte ballooning scores in biopsy-proven NAFLD patients (AUROC ranging from 0.724 to 0.759).…”
Section: Extracellular Matrixmentioning
confidence: 99%
See 3 more Smart Citations